2013
DOI: 10.1519/jsc.0b013e3182651d79
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Pelvic and Hip Flexibility in Men and Women Matched for Sit-and-Reach Score

Abstract: The purpose of this study was to test sex differences in sagittal plane thoracic (T), lumbar (L), and pelvic (P) angles measured during the sit-and-reach (SR) test and hip joint angle during a passive straight leg raise (SLR) test in men and women matched for SR scores. Thirty-five men and 35 women performed a standard SR and SLR test. Among the 70 subjects, 25 male and female pairs were identified using <5% difference in the SR score as the pairing criterion. Both SR and SLR tests were videotaped and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The sit-and-reach test is a common measure of flexibility, and specifically measures the flexibility of the lower back and hamstring muscles. Previous research has suggested that women have more flexibility in this area than do men [30], [31].…”
Section: Discussionmentioning
confidence: 97%
“…The sit-and-reach test is a common measure of flexibility, and specifically measures the flexibility of the lower back and hamstring muscles. Previous research has suggested that women have more flexibility in this area than do men [30], [31].…”
Section: Discussionmentioning
confidence: 97%
“…The PSLR test is considered the standard assessment for hamstring extensibility and is one of the most widely used measure-ments in both clinical and research settings [2,6,23]. In this line, several studies have examined the validity of the classic or modified SR test for assessing hamstring extensibility, using the PSLR test as the criterion measure [1,6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the involvement of other muscles such as the mono-articular gluteus maximus should be negligible. Another possible reason is the variation in the pelvic position [22,23] and stiffness of non-muscular tissue such as nerve, fascia, and tendon [27]. Further studies are warranted to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Passive stretching is a commonly observed clinical intervention for reduced hamstring extensibility [21], and the passive straight leg raise (PSLR) test is one of the most commonly used tests for evaluating hamstring muscle extensibility [14,18,23,28,29,34]. Furthermore, because of its reliability and validity, the PSLR test has been extensively used as the gold standard in studies evaluating several hamstring extensibility tests [2,15,16,18,19,27,39], for which the instrument of evaluation was the Unilever inclinometer (ISOMED, Inc., Portland, OR, USA) [2,18,19,27,38].…”
Section: Introductionmentioning
confidence: 99%